REGULATIONS ON THE VALIDATION OF MARRIAGE AGREEMENTS CARRIED OUT BY NOTARIES IN INDONESIAN POSITIVE LAW FOLLOWING CONSTITUTIONAL COURT DECISION NUMBER 69/PUU-XIII/2015 - Safira Annisa; Djumikasi; Yenny Eta Widyanti (CV. RADJA PUBLIKA, 2025)
The changes that occurred in the Constitutional Court Decision Number 69/PUU-XIII/2015 caused multiple interpretations, the change of the phrase